2015
DOI: 10.1111/bph.13211
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic targets of triple‐negative breast cancer: a review

Abstract: Breast cancer (BC) is the second most common cause of cancer deaths. Triple-negative breast cancer (TNBC) does not show immunohistochemical expression of oestrogen receptors, progesterone receptors or HER2. At present, no suitable treatment option is available for patients with TNBC. This dearth of effective conventional therapies for the treatment of advanced stage breast cancer has provoked the development of novel strategies for the management of patients with TNBC. This review presents recent information a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
126
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(130 citation statements)
references
References 72 publications
(73 reference statements)
2
126
0
2
Order By: Relevance
“…The Wnt receptor frizzled-7 (FZD7) and co-receptor the low-density lipoprotein receptor-related protein-6 (LRP6) expression increased significantly in triple-negative breast cancer. Moreover, the transcriptional knockdown of FZD7 or LRP6 in triple-negative breast cancer cells represses tumor growth (Jamdade et al, 2015). Accumulating evidence demonstrated that activated Wnt/ -catenin signaling participates in the pathological process of breast cancer (King et al, 2012;Lu and Li, 2014;Ma et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The Wnt receptor frizzled-7 (FZD7) and co-receptor the low-density lipoprotein receptor-related protein-6 (LRP6) expression increased significantly in triple-negative breast cancer. Moreover, the transcriptional knockdown of FZD7 or LRP6 in triple-negative breast cancer cells represses tumor growth (Jamdade et al, 2015). Accumulating evidence demonstrated that activated Wnt/ -catenin signaling participates in the pathological process of breast cancer (King et al, 2012;Lu and Li, 2014;Ma et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Since m-TOR pathway not only plays a key role in glycolysis, but also acts as therapeutic target of TNBC [26], we further examined the effect of curcumin on m-TOR phosphorylation in MDA-MB-231 cells. Curcumin alone partly reduced phosphroylated m-TOR.…”
Section: Discussionmentioning
confidence: 99%
“…The level of BMP and Hedgehog signalling was higher in triple negative than triple positive tumours that may also be facilitated by short variants or the balance of full length and shorter variants in these tumours. Enhanced Wnt signalling and Notch signalling has also been reported to play a role in triple negative tumours (Jamdade VS et al 2015;Koval A et al 2016;King TD et al 2012) although Wnt signalling is believed to be promoted by full length Sulf1 and Sulf2 genes.…”
Section: Discussionmentioning
confidence: 99%